KATEKESE UPAYA SUKSESI PERTUMBUHAN IMAN UMAT PAROKI HSPMTB-PUTUSSIBAU - Dius, Egi (Jurnal Euntes, 2024)
The focus of this research is to examine the faith growth of the people in HSPMTB-Putussibau Parish. Cultural and economic issues are the main challenges in achieving ideal faith growth. Based on the results of interviews and observations and assisted by James Fowler's theory of faith development as a scalpel in analysing the results of this study found that the HSPMTB-Puttussibau parishioners have not achieved ideal faith growth. This reality raises awareness of the importance of means and efforts to grow the faith of the people and understanding of the faith that is lived. Catechesis is one of the means of succession to help the faith growth of the people.